Statement from the Asia Summit: Current state of arrhythmia care in Asia - Wataru Shimizu; Fred M. Kusumoto; Michael‐Joseph F. Agbayani; Sirin Apiyasawat; Minglong Chen; Chi Keong Ching; Jong‐Il Choi; Van Buu Dan Do; Dicky A. Hanafy; Jodie L. Hurwitz; Sofian Johar; Jonathan M. Kalman; et al. (Journal of Arrhythmia, 2024)
Abstract On May 27, 2022, the Asia Pacific Heart Rhythm Society and the Heart Rhythm Society convened a meeting of leaders from different professional societies of healthcare providers committed to arrhythmia care from the Asia Pacific region. The overriding goals of the meeting were to discuss clinical and health policy issues that face each country for providing care for patients with electrophysiologic issues, share experiences and best practices, and discuss potential future solutions. Participants were asked to address a series of questions in preparation for the meeting. The format of the meeting was a series of individual country reports presented by the leaders from each of the professional societies followed by open discussion. The recorded presentations from the Asia Summit can be accessed at https://www.heartrhythm365.org/URL/asiasummit‐22. Three major themes arose from the discussion. First, the major clinical problems faced by different countries vary. Although atrial fibrillation is common throughout the region, the most important issues also include more general issues such as hypertension, rheumatic heart disease, tobacco abuse, and management of potentially life‐threatening problems such as sudden cardiac arrest or profound bradycardia. Second, there is significant variability in the access to advanced arrhythmia care throughout the region because of differences in workforce availability, resources, drug availability, and national health policies. Third, collaboration in the area already occurs between individual countries, but no systematic regional method for working together is present.